Crystal size distribution and residence time in mafic rocks of the La Repartición Complex, San Luis Potosí, Mexico - Torres Sanchez, Dario; Soto Ramírez, Daniel (JOURNAL OF BASIC SCIENCES, 2025)
La Repartición Volcanic Field (LRVF), located in the northeastern portion of the San Luis Potosí Volcanic Field, presents a variety of volcanic rock types, highlighting it as an exemplary natural laboratory for petrological analysis. Therefore, the present work aims to perform crystal size distribution (CSD) analyses and residence time calculations on plagioclase microcrystals from mafic rocks to understand the formation time and textural variation of these minerals in magmatic reservoirs. Petrographic analyses revealed that the analyzed samples present a mineralogical assemblage of olivine, pyroxene, and plagioclase embedded in a glassy matrix. CSD analyses exhibit steep slopes for all analyzed samples, and residence times indicate an approximate of 3 years, which suggests a rapid ascent of magmas to the surface at upper levels of the continental crust.